Platelet glycoproteins associated with aspirin‐treatment upon platelet activation. Issue 6 (12th September 2016) - Shah, Punit; Yang, Weiming; Sun, Shisheng; Pasay, Jered; Faraday, Nauder; Zhang, Hui
Abstract : Platelet glycoproteins are known to play central roles in hemostasis and vascular integrity and have pathologic roles in vascular occlusive diseases such as myocardial infarction and stroke. Characterizing glycoproteins within and secreted by platelets can provide insight into the mechanisms that underlie vascular pathologies and the therapeutic benefits or failure of anti‐platelet agents. To study the impact of aspirin, which is commonly prescribed for primary and secondary cardiovascular prevention, on the platelet glycoproteome, we evaluated washed platelets from ten donors. The platelet glycoproteome, was studied using an iTRAQ in resting and stimulated states and with and without aspirin treatment. Using solid phase extraction of glycosite‐containing peptides (SPEG), we were able to identify 799 unique N‐linked glycosylation sites (glycosites) in platelets, representing the largest and the most comprehensive analysis to date. We were able to identity a number of glycoproteins impacted by aspirin treatment, which we validated using global proteomics analysis of platelets and their secreted proteins. In our analyses, metallopeptidase inhibitor 1 (TIMP1) was the single most significantly affected glycoprotein by aspirin treatment. ELISA assays confirmed proteomic results and validated our strategy. Functional analysis demonstrated that TIMP1 levels were highly correlated with platelet reactivity in vitro, with a correlation coefficient of −0.5. The release of TIMP1 from platelets, which was previously unknown to be affected by aspirin treatment, may play important roles in hemostasis and/or vascular integrity. If validated, our findings may be useful for developing assays that assess platelet response to aspirin or other anti‐platelet therapies.